Numerical Modelling of Hybrid Polymer Composite Frame for Selected Construction Parts and Experimental Validation of Mechanical Properties - Akshat, Tegginamath; Petru, Michal; Mishra, Rajesh Kumar (Polymers, 2025)
This article is a numerical and experimental study of the mechanical properties of different glass, flax and hybrid composites. By utilizing hybrid composites consisting of natural fibers, the aim is to eventually reduce the percentage usage of synthetic or man-made fibers in composites and obtain similar levels of mechanical properties that are offered by composites using synthetic fibers. This in turn would lead to greener composites being utilized. The advantage of which would be the presence of similar mechanical properties as those of composites made from synthetic fibers along with a reduction in the overall weight of components, leading to much more eco-friendly vehicles. Finite element simulations (FEM) of mechanical properties were performed using ANSYS. The FEM simulations and analysis were performed using standards as required. Subsequently, actual beams/frames with a defined geometry were fabricated for applications in automotive body construction. The tensile performance of such frames was also simulated using ANSYS-based models and was experimentally verified. A correlation with the results of the FEM simulations of mechanical properties was established. The maximum tensile strength of 415 MPa was found for sample 1: G-E (glass-epoxy composite) and the minimum strength of 146 MPa was found for sample 2: F-G-E (G-4) (flax-glass-epoxy composite). The trends were similar, as obtained by simulation using ANSYS. A comparison of the results showed the accuracy of the numerical simulation and experimental specimens with a maximum error of about 8.05%. The experimental study of the tensile properties of polymer matrix composites was supplemented with interlaminar shear strength, and a high accuracy was found. Further, the maximum interlaminar shear strength (ILSS) of 18.5 MPa was observed for sample 1: G-E and the minimum ILSS of 17.0 MPa was observed for sample 2: F-G-E (G-4). The internal fractures were analyzed using a computer tomography analyzer (CTAn). Sample 2: F-G-E (G-4) showed significant interlaminar cracking, while sample 1: G-E showed fiber failure through the cross section rather than interlaminar failure. The results indicate a practical solution of a polymer composite frame as a replacement for existing heavier components in a car, thus helping towards weight reduction and fuel efficiency.
Keywords: tensile test; finite element modeling (FEM); computed tomography; mechanical properties; interlaminar shear strength (ILSS); hybrid composite